Representation of Religious Conflict in Local Media - Encep Dul Wahab; Darajat Wibawa; Enjang Muhaemin; Dyah Rahmi Astuti (Journal of Islamic World and Politics, 2022)
The media always try their best to represent reality for their audiences, with the hope of retaining readers and increasing company revenues. However, in depicting the reality of religious conflict, the media often contradicts the norms, ethics, and code of ethics of journalism itself. The purpose of this study was to determine the representation of religious conflict in local media, namely the Ahmadiyah conflict in West Java, which was published in the Pikiran Rakyat in news coverage from 2010 to 2011. This study used Teun A. van Dijk's critical discourse analysis method. The results of the study show that Pikiran Rakyat represents the Ahmadiyah conflict in various ways, including dividing the object of its reporting into two camps, strong and weak, by branding Ahmadiyah as a deviant, banned, and disbanded organization. The strong side is an organization supported by the government, and the weak side is Ahmadiyah, which does not receive government protection and support. Pikiran Rakyat presents news sources in this religious conflict in an unfair and balanced manner, presenting more news sources from the majority than Ahmadiyah as a minority. Pikiran Rakyat also represents ways of resolving the Ahmadiyah conflict.